Adaptive Modulation and Superposition Coding for MIMO Data Transmission Using Unequal Error Protection and Ordered Successive Interference Cancellation Techniques - Saad, Wasan Kadhim; Jabbar, Waheb A.; Hamza, Bashar J. (JCM, 2019)
This paper proposes and discusses an efficient multiple input multiple output (MIMO) system for adaptive modulation coding (AMC) based on unequal error protection (UEP) and superposition coding (SPC) by exploiting the features of sub channel partitioning. Using AMC, an appropriate order of modulation and code rate to suit the channel state information (CSI) can be selected. The realization of UEP is achieved through adaptive allocation and transmission of high and low-priority data signals over high and low quality sub channels respectively. A multistage decoding (MSD) receiver with the ordered successive interference cancellation (OSIC) technique is employed in the receiver by using two linear receiver signal combiner (RSC) techniques: zero-forcing (ZF) and minimum mean square error (MMSE). The data priority can be distinguished by the signal-to-noise ratio (SNR) and can be categorized as mode-B and mode-G. The simulation results show that the SNR performance enhancement for the UEP- MIMO scheme is approximately 9.4 dB compared to the others schemes. In addition, for the UEP-MIMO scheme, the overall data system transmission from mode-B outperforms that of mode-G with SNR gains of 8.2 dB compared to the 7.5 dB for the UEP-SISO scheme. Also, MMSE-SPC also outperforms the ZF-SPC with a 3 dB SNR at a bit error rate (BER) of 10-3.